2020
DOI: 10.5382/econgeo.4741
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Group Element Enrichment of Natural Quenched Sulfide Solid Solutions, the Norilsk 1 Deposit, Russia

Abstract: The deepest terminations of the Mount Rudnaya subvertical massive sulfide offshoots of the Norilsk 1 orebody are composed of exceptionally fine grained sulfides that are believed to be natural quenched sulfide solid solutions. Copper-rich intermediate solid solution (ISS) and Fe-rich monosulfide solid solution (MSS) form an equigranular and lamellar matrix hosting MSS- and ISS-dominant globules. The nonstoichiometric chemical compositions of the solid solutions plot within their high-temperature fields known f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…The authors proposed that Pd-rich pentlandite formed by a peritectic reaction of MSS + Liquid = PnSS, where PnSS is a high-temperature solid solution from which pentlandite is obtained upon cooling [43,45]. In addition, Brovchenko and coauthors found 0.04-4.62 wt.% Pd in pentlandite from Norilsk-1 deposit and similarly came up with a peritectic reaction as plausible explanation for this atypical pentlandites [12]. Accordingly, there are four main hypotheses, which have been proposed to explain the high concentrations of palladium in pentlandite.…”
Section: Genetic Constraints and Mechanisms For The Enrichment Of Pd In Pentlanditementioning
confidence: 98%
See 4 more Smart Citations
“…The authors proposed that Pd-rich pentlandite formed by a peritectic reaction of MSS + Liquid = PnSS, where PnSS is a high-temperature solid solution from which pentlandite is obtained upon cooling [43,45]. In addition, Brovchenko and coauthors found 0.04-4.62 wt.% Pd in pentlandite from Norilsk-1 deposit and similarly came up with a peritectic reaction as plausible explanation for this atypical pentlandites [12]. Accordingly, there are four main hypotheses, which have been proposed to explain the high concentrations of palladium in pentlandite.…”
Section: Genetic Constraints and Mechanisms For The Enrichment Of Pd In Pentlanditementioning
confidence: 98%
“…Pentlandite is the only palladium concentrator among the base metal sulfide minerals of the nickel-copper ores, since palladium is a compatible element with pentlandite while incompatible to coexisting pyrrhotite, chalcopyrite and cubanite [1][2][3][4][5][6][7][8][9][10][11][12]. Pentlandite is considered a late-forming mineral, within the base metal sulfides assemblage, that may be formed as a result of exsolution of MSS and ISS.…”
Section: Genetic Constraints and Mechanisms For The Enrichment Of Pd In Pentlanditementioning
confidence: 99%
See 3 more Smart Citations